2020
DOI: 10.1007/s11916-020-00853-z
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine in Enhanced Recovery After Surgery (ERAS) Protocols for Postoperative Pain

Abstract: Purpose of Review Effective acute pain management has evolved considerably in recent years and is a primary area of focus in attempts to defend against the opioid epidemic. Persistent postsurgical pain (PPP) has an incidence of up to 30-50% and has negative outcome of quality of life and negative burden on individuals, family, and society. The 2016 American Society of Anesthesiologists (ASA) guidelines states that enhanced recovery after surgery (ERAS) forms an integral part of Perioperative Surgical Home (PSH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
130
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(143 citation statements)
references
References 74 publications
(101 reference statements)
5
130
0
8
Order By: Relevance
“…Similar findings were reported when dexmedetomidine infusion was used before operations on children undergoing hernia repair [30]. Currently, usage of dexmedetomidine in the perioperative period has shown to significant ly improve outcomes in the postoperative period especially when used in the enhanced recovery after surgery protocols were accompanied with less time of discharge from PACU and better patient's satisfaction [31].…”
Section: Discussionsupporting
confidence: 71%
“…Similar findings were reported when dexmedetomidine infusion was used before operations on children undergoing hernia repair [30]. Currently, usage of dexmedetomidine in the perioperative period has shown to significant ly improve outcomes in the postoperative period especially when used in the enhanced recovery after surgery protocols were accompanied with less time of discharge from PACU and better patient's satisfaction [31].…”
Section: Discussionsupporting
confidence: 71%
“…Our results agreed with previous reviews that reported that DEX played an essential role as an opioid alternative in multimodal analgesia that formed part of ERAS care. 2,3,5 Ge et al 12,13 showed the benefits of intraoperative DEX infusion in terms of lower VAS scores, reduced morphine consumption, and decreased numbers of pain-induced IV-PCA pump presses during the first 24 hours after abdominal colectomy and hysterectomy. Xu et al 14 also reported similar outcomes on postoperative pain in patients treated with DEX during abdominal hysterectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in this present study, we administered DEX as continuous infusion, without a loading dose. According to the product information, the recommended rate of maintenance infusion of DEX for sedation is 0.2‐0.7 mcg/kg/h 5 . Adjunctive DEX infusion at a relatively slow rate of 0.4 mcg/kg/h has previously been used to maintain GA in patients undergoing abdominal surgery and was found to relieve acute postoperative pain effectively 12,13,19,24 .…”
Section: Discussionmentioning
confidence: 99%
“…The α2 agonist agents can reduce norepinephrine secretion by stimulating peripheral α 2 presynaptic receptors. In addition, the most important mechanism of dexmedetomidine in penile erection prevention may be due to its α 2 -adrenoceptor agonistic property by acting on vascular smooth muscle enhancing vasoconstriction in peripheral arteries to prevent erections (8,9,(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%